The evaluation of the antibacterial capacity of tea tree functionalized microcapsules in textiles - Negreiros, Talita Nicolau Oliveira Vidal (2022)
The textile industry develops products that go beyond aesthetic concerns. Manufacturers functionalize these new textile products to provide them with new technical properties, to meet and even exceed user needs. The technical properties are diverse, from ultraviolet protection to antimicrobial or self-cleaning properties. The growth of microorganisms on textiles can result in unpleasant odors, stains or even accelerate the wear and tear of textile products. Microcapsules may contain natural or synthetic components in their core, capable of providing the desired properties to textiles (Figure 1). In addition, a shell protects the core and its design allows a gradual release of the main component. In this work, microcapsules were dyed to prevent the appearance of stains. This research tested the antibacterial capacity of microcapsules functionalized with tea tree essential oil on polyester fabric (PES). The fabric was tested with dyed and undyed microcapsules to ensure no dye interference. This research evaluates antibacterial capacity using the following standard bacteria: Staphylococcus aureus and Escherichia coli.